2019
DOI: 10.11113/ijbes.v6.n1-2.396
|View full text |Cite
|
Sign up to set email alerts
|

Millennial Tourist Emotional Experience in Technological Engagement at Destination

Abstract: Millennial is known to be the generations that strongly empowered by technologies that apparently had altered the pattern of their consumption habits to shape a new form of tourist market. The great incursion of technology on Millennial does not only mediates the experience formation at destination, instead provide added value and emotional impact through its cognitive stimulation and experience co-creation possibilities. As the key instrument for experience enhancement, mobile technologies support users' need… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 26 publications
1
9
0
1
Order By: Relevance
“…Gen Y respondents have confirmed they experience, to a greater extent, negative feelings and emotions, which is one of the characteristic features of nomophobia [68,70,71,74]. This situation occurs mainly among the youngest age segment (16)(17)(18)(19), while the older age groups claim to experience greater indifference. It can be concluded that as their years of coexistence with the web 2.0 model decrease, their emotional involvement with the use of smartphones during travel also decreases.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Gen Y respondents have confirmed they experience, to a greater extent, negative feelings and emotions, which is one of the characteristic features of nomophobia [68,70,71,74]. This situation occurs mainly among the youngest age segment (16)(17)(18)(19), while the older age groups claim to experience greater indifference. It can be concluded that as their years of coexistence with the web 2.0 model decrease, their emotional involvement with the use of smartphones during travel also decreases.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the tourist functionalities under analysis [84], most users claimed to use them frequently, being "Learn about destination" the least used. There are also intragroup differences in this regard, because the youngest age group (16)(17)(18)(19) uses these functions the least, suggesting an area of opportunity for DMOs, which can enhance the use of these functionalities to influence the feelings and emotions Gen Y associate with smartphone use during travel. In fact, the results allude to a behavior among the youngest segment of the Gen Y that suggests that their smartphone use for non-tourism purposes during travel sometimes generates negative emotions and feelings.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Technology has transformed ways of how experiences are created (Crouch and Desforges, 2003) and it turned travelers into experience seekers. Millennials and Generation Z have played a significant role in this paradigm shift (Mohd et al, 2019), which leads to the development of digital tourism ecosystems (Benckendorff, Xiang and Sheldon, 2019, 22). Although tourist experiences are still only rudimentarily understood, they require further investigation (Cutler and Carmichael, 2010; Larsen et al, 2019) and are even questionable to some degree (Gretzel and Jamal, 2009), although some of them have already been technology-mediated (Tussyadiah and Fesenmaier, 2009).…”
Section: Achieving Competitive Advantage With Technologyenhanced Tourist Experiencementioning
confidence: 99%